2017
DOI: 10.1073/pnas.1702469114
|View full text |Cite
|
Sign up to set email alerts
|

Traces of surfactants can severely limit the drag reduction of superhydrophobic surfaces

Abstract: Superhydrophobic surfaces (SHSs) have the potential to achieve large drag reduction for internal and external flow applications. However, experiments have shown inconsistent results, with many studies reporting significantly reduced performance. Recently, it has been proposed that surfactants, ubiquitous in flow applications, could be responsible by creating adverse Marangoni stresses. However, testing this hypothesis is challenging. Careful experiments with purified water already show large interfacial stress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
162
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(188 citation statements)
references
References 44 publications
18
162
8
Order By: Relevance
“…Similarly, (28) report: u I ≈ 8 × 10 −2 for 5 mm long lanes (see their figure 3b), which is significantly reduced compared with the theoretical (surfactant-free) prediction; and u I ≈ 8 × 10 −3 for 15 mm long lanes ( figure 5), which is practically negligible. The main difficulty in applying our theoretical model, for instance to predict the reduced slip velocities measured experimentally by (27) and (28), is that the surfactant properties and their concentrations are completely unknown in their experiments. Instead, we use our model to predict the concentration of surfactant, for three different possible surfactant types, which could lead to the measured u I reported in (27) and (28).…”
Section: C2 Limit Of Small Gap Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, (28) report: u I ≈ 8 × 10 −2 for 5 mm long lanes (see their figure 3b), which is significantly reduced compared with the theoretical (surfactant-free) prediction; and u I ≈ 8 × 10 −3 for 15 mm long lanes ( figure 5), which is practically negligible. The main difficulty in applying our theoretical model, for instance to predict the reduced slip velocities measured experimentally by (27) and (28), is that the surfactant properties and their concentrations are completely unknown in their experiments. Instead, we use our model to predict the concentration of surfactant, for three different possible surfactant types, which could lead to the measured u I reported in (27) and (28).…”
Section: C2 Limit Of Small Gap Lengthmentioning
confidence: 99%
“…[16][17][18][19][20][21], as well as low-Reynolds-number, internal flows, which are the focus of the present paper (e.g. 9,11,[22][23][24][25][26][27][28]. At low Reynolds numbers, the use of SHSs has been proposed to reduce what are otherwise very large pressure differences across microchannels, as is the case in microfluidic devices or in micro-cooling applications (29)(30)(31), as well as to minimize Taylor dispersion in the chemical or biological analysis of species (10).…”
Section: Introductionmentioning
confidence: 99%
“…As the size of the system decreases, interfacial contributions become increasingly relevant. Microfluidic experiments revealed for instance that traces of surfactants can severely limit the drag reduction of superhydrophobic surfaces [10]. Impurities at the water-air interface have also been shown to affect its viscoelastic response in AFM experiments [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There is now mounting evidence that contamination by surfactants, even in trace amounts (Peaudecerf et al 2017), can immobilize superhydrophobic surfaces, rendering them, essentially, no-slip surfaces. Kim & Hidrovo (2012) performed experiments in a rectangular microchannel with regular sidewall patterning to visualize the location of the air-water interface within the roughness elements.…”
Section: Introductionmentioning
confidence: 99%
“…Bolognesi et al (2014) suggested surfactants or other surface contaminants as possible causes for this surface immobilization. In a very recent study, Peaudecerf et al (2017) focused on examining the effect of surfactants on hydrodynamic slip in longitudinal flows along unidirectionally patterned surfaces. Careful pressure control was used to maintain flat menisci, with the conclusion that even trace amounts of surfactants can cause a dramatic reduction in the expected slip enhancement properties of the surfaces, again, by causing an immobilization of these surfaces into effective no-slip zones.…”
Section: Introductionmentioning
confidence: 99%